The Road to Recovery #3: Facilitating Community Resilience for Effective Pandemic Response - Cody Gusto; Colby Silvert; John Diaz (EDIS, 2021)
This third publication in the Road to Recovery series provides information and recommendations to support Extension professionals' ability to facilitate capacity building and resilience development for communities during COVID-19 and potential future pandemic situations. This new 5-page publication of the UF/IFAS Department of Agricultural Education and Communication was written by Cody Gusto, Colby Silvert, and John Diaz. https://edis.ifas.ufl.edu/wc380